Dynamics of loops at the substrate entry channel determine the specificity of iridoid synthases - Sandholu, Anand S.; Mohole, Madhura; Duax, William L.; Thulasiram, Hirekodathakallu V.; Sengupta, Durba; Kulkarni, Kiran (Febs Letters, 2018)
Iridoid synthases belong to the family of short-chain dehydrogenase reductase involved in the biosynthesis of iridoids. Despite having high sequence and structural homology with progesterone 5 beta- reductase, these enzymes exhibit differential substrate specificities. Previously, two loops. L1 and L2 at substrate-binding pocket, were suggested to be involved in generating substrate specificity. However, the structural basis of specificity determinants was elusive. Here, combining sequence and structural analysis, site-directed mutagenesis, and molecular dynamics simulations, we have shown that iridoid synthase contains two channels for substrate entry whose geometries are altered by L1-L2 dynamics, primarily orchestrated by interactions of residues Glu161 and Gly162 of L1 and Asn358 of L2. A complex interplay of these interactions confer the substrate specificity to the enzyme.
Keywords: iridoid synthase; iridoids; Molecular dynamics simulations; progesterone 5 beta-reductase; Substrate specificity